Hughes-Stovin syndrome: a case report and literature review - Nazir, Imran; Alrubai, Elham Hamed; Iqbal, Muhammad Zafar; Ahmad Elimam, Amani Abdulmoniem; Ahmad Elimam, Amal Abdulmoniem; Ezzat, Sadeen Essam; Aseeri, Thekra A.; Alqethami, Sara Salem; Algoufi, Jumanah Faisal; Rahman , Sayed S. (International Journal of Research in Medical Sciences, 2025)
Hughes-Stovin syndrome (HSS) is a rare clinical entity comprised of thrombophlebitis and multiple pulmonary and bronchial aneurysms. Medical literature has documented fewer than 40 cases of HSS. Its pathogenesis and etiology are still unknown. It is considered a variant of Behcet’s disease (BD). HSS is being managed either medically or surgically. We report the case of a 32-year-old Saudi male patient with HSS who initially presented with a pulmonary embolism (PE). Later, he developed hemoptysis that was treated successfully with methylprednisolone. The genetic, etiologic, and pathologic basis of HSS should be explored more in the future to elucidate the disease. Exploration of better and optimal medical and surgical therapeutic regimens is a need for time to treat and prevent morbidity in BD and HSS. There is a dilemma of anticoagulation in these patients that needs to be addressed and investigated properly.